Beyond the tolerance/intolerance dichotomy: incorporating attitudes and acceptability into a robust definition of social tolerance of wildlife. Issue 3 (3rd May 2020) - Brenner, Lara J.; Metcalf, Elizabeth Covelli
ABSTRACT: While most wildlife researchers and managers agree that human tolerance is critical in determining the success and persistence of wildlife populations, the concept of tolerance has lacked definitional precision and operational consistency in the literature. This inconsistency has opened the door to a multiplicity of human-wildlife tolerance studies that present tolerance as either an attitude, a normative belief, or a behavioral intention, making it difficult to compare results across study systems. We drew upon foundational human dimensions of wildlife, sociology, and animal behavior studies to propose an integrated framework of human-wildlife tolerance, defined here as "accepting wildlife and/or wildlife behaviors that one dislikes." This definition clarifies the term "tolerance" by incorporating attitudes and acceptability (antecedents of behavior) as two distinct but interrelated axes. We also develop a typology framework that will provide insight into changing responses to human-wildlife conflict, and help evaluate future tolerance-boosting policy or educational interventions.